ECONOMIC MECHANISMS FOR IMPROVING THE EFFICIENCY OF FOREIGN CREDIT LINES (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the economic mechanisms for improving the efficiency of foreign credit line utilization. It examines key factors such as resource allocation, institutional quality, financial intermediation, and monitoring systems. The study also reviews international experience and evaluates recent reforms in Uzbekistan related to the use of foreign financial resources. The findings indicate that efficiency depends on strategic allocation and effective management of credit resources.